Particularidades del procedimiento laboral en el contexto del Código Orgánico General de Procesos (COGEP) [Tema Central] - Abad Arévalo, Dana Mirosava (2015)
A transcendental aspect that must be taken into account related to the recent procedural reforms is that with COGEP has established a new abbreviated procedure for all labor cases. This means that in first instance, these cases will be comprised of a single hearing to address any procedural defects, submit and analyze evidence and rule on the matter. The objective of this article is to show the disadvantages that opting for such a procedure carries in practice for not being adequate for all labor cases, mainly for the complexity of some cases and the apparent inability of judges and lawyers to tackle all those issues in a single hearing.